Aktualisasi Asas-Asas Umum Pemerintahan yang Baik dalam Sistem Penyelenggaraan Pemerintahan - Sapada, Andi Tenri; Rezah, Farah Syah (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study aims to examine the actualization of general principles of good governance in the government administration system at Bone Regency. The type of research used is empirical research. Data collection techniques used in this study were interviews and literature study. The research data were analyzed quantitatively and then presented descriptively. The results showed that the actualization of general principles of good governance in the government administration system at Bone Regency is still not implemented. One of the main reasons is that the professionalism and competence of SCA resources in Bone Regency are still low. Furthermore, the factors that influence realizing the general principles of good governance in the government administration system at Bone Regency include leadership capability, supervision, SCA resources, and consensus between government and citizens. Therefore, substantial efforts are needed to improve the professionalism and competence of SCA resources through education and the provision of special training. In addition, leadership capability, supervision, and consensus between government and citizens also need to be improved and carried out consistently so that the actualization of general principles of good governance in the government administration system at Bone Regency can be carried out well in the future.